Studi Pelaksanaan Kurikulum Merdeka pada SMK Amaliah 2 Ciawi Bogor - Siti Nurafifah; Chaira Saidah Yusrie; Riyanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the implementation of the Independent Curriculum at SMK Amaliah 2 Ciawi Bogor. The Independent Curriculum, initiated by the Ministry of Education, Culture, Research, and Technology, focuses on flexible and student-centered learning. This study uses a descriptive method with a qualitative approach. Data were collected through interviews, observations, and documentation. The results of the study indicate that the implementation of the Independent Curriculum at SMK Amaliah 2 faces several challenges, especially in terms of teacher adaptation to new approaches, infrastructure readiness, and student understanding of the learning system. However, this curriculum provides students with more freedom in choosing subjects and projects that suit their interests and talents, and encourages independence in the learning process.